1999
DOI: 10.1038/4580
|View full text |Cite
|
Sign up to set email alerts
|

Predictive coding in the visual cortex: a functional interpretation of some extra-classical receptive-field effects

Abstract: We describe a model of visual processing in which feedback connections from a higher- to a lower-order visual cortical area carry predictions of lower-level neural activities, whereas the feedforward connections carry the residual errors between the predictions and the actual lower-level activities. When exposed to natural images, a hierarchical network of model neurons implementing such a model developed simple-cell-like receptive fields. A subset of neurons responsible for carrying the residual errors showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

277
4,549
14
8

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 4,609 publications
(4,848 citation statements)
references
References 44 publications
277
4,549
14
8
Order By: Relevance
“…Additionally, it is easy to imagine that the dopamine-like priming mechanism we have hypothesized here not only enhances contours, but may play an integral part in training the system in a similar manner as suggested in Rao and Ballard (1999). For instance, it has been proposed that observed movement of objects trains neurons to recognize contours (Prodöhl et al 2003).…”
Section: Extending Dopamine To Temporal Contours Via Td (Dimensions)mentioning
confidence: 73%
See 1 more Smart Citation
“…Additionally, it is easy to imagine that the dopamine-like priming mechanism we have hypothesized here not only enhances contours, but may play an integral part in training the system in a similar manner as suggested in Rao and Ballard (1999). For instance, it has been proposed that observed movement of objects trains neurons to recognize contours (Prodöhl et al 2003).…”
Section: Extending Dopamine To Temporal Contours Via Td (Dimensions)mentioning
confidence: 73%
“…Our model agrees with these observations since build up of group suppression increases endstop detection and would also create a delay for such detection as suppression builds. This is also similar to the model by Rao and Ballard (1999), which used a predictive feedback suppression mechanism to facilitate end-stop detection.…”
Section: Fig 17mentioning
confidence: 76%
“…Previous studies (Clos et al., 2014; Sohoglu & Davis, 2016; Sohoglu et al., 2012; Tuennerhoff & Noppeney, 2016) have suggested that predictive coding (Friston, 2005; Huang & Rao, 2011; Mumford, 1992; Rao & Ballard, 1999) underlies the instant increase in intelligibility of distorted speech signals when these are presented simultaneously with or immediately after the presentation of the disambiguating stimulus (e.g., a written or intact auditory counterpart of the speech stimulus). The predictive coding framework proposes that information residing in an internal predictive model is fed back from higher‐order cortical areas to lower‐level brain areas whose activity reflects the difference between auditory input and the predictive information, that is, the prediction error signal (Friston, 2005; Huang & Rao, 2011; Mumford, 1992; Rao & Ballard, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The predictive coding framework proposes that information residing in an internal predictive model is fed back from higher‐order cortical areas to lower‐level brain areas whose activity reflects the difference between auditory input and the predictive information, that is, the prediction error signal (Friston, 2005; Huang & Rao, 2011; Mumford, 1992; Rao & Ballard, 1999). This error signal is projected to the higher‐order cortical areas through feedforward connections to update the internal model.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in computational neuroscience have shown that relatively simple models of developmental visual systems are capable of developing qualitatively similar properties to those found in the early stages of visual processing in cats and monkeys (Hancock et al, 1992;Field, 1994;Olshausen and Field, 1996;Rao and Ballard, 1999). However, those models often use images from publicly available databases or photographs taken in a natural environment as visual stimuli, and do not allow the system to freely interact with the environment and choose those sensory events.…”
Section: Introductionmentioning
confidence: 99%